2 States: The Story of My Marriage
Love marriages around the world are simple: Boy loves girl. Girl loves boy. They get married. In India, there are a few more steps: Boy loves Girl. Girl loves Boy. Girl\'s family has to love boy. Boy\'s family has to love girl. Girl\'s Family has to love Boy\'s Family. Boy\'s family has to love girl\'s family. Girl and Boy still love each other. They get married. Welcome to 2 States, a story about Krish and Ananya. They are from two different states of India, deeply in love and want to get married. Of course, their parents don t agree. To convert their love story into a love marriage, the couple have a tough battle in front of them. For it is easy to fight and rebel, but it is much harder to convince. Will they make it? From the author of blockbusters Five Point Someone, One Night @ the Call Center and The 3 Mistakes of My Life, comes another witty tale about inter-community marriages in modern india.